Mykola Pavlovych Grytsai - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is dedicated to the doctor of medical sciences, professor Hrytsai Mykola Pavlovich.